2022
DOI: 10.1088/1361-6463/ac9149
|View full text |Cite
|
Sign up to set email alerts
|

Tetragonal distortion modified magnetism and anomalous Hall effect of Mn2CoAl Heusler alloys through Ar ion irradiation

Abstract: Tetragonal Heusler alloys are attracting more attention owing to their great scientific and technological interest in spintronics. However, the crystal structures of most Heusler alloys are cubic. One feasible method to obtain tetragonal Heusler alloy is to manipulate the out-of-plane distortion of cubic Heusler alloys. In this work, we report the ion irradiation-induced tetragonal distortion in Mn2CoAl Heusler films. The out-of-plane lattice constant continuously increases from 5.84 to 6.09 Å, while the in-pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…For tetragonal X 3 Z (Z = Al, Ga, In Tl, Si, Ge, Sn, Pb) alloys, the X(A), X(B), X(C) and Z atoms occupy the (0, 0, 0), (0.25, 0.25, 0.25), (0.5, 0.5, 0.5) and (0.75, 0.75, 0.75) Wyckoff positions, respectively [22]. Thus, Chen et al [51] detected meta-stable tetragonal phase formation in Mn 2 CoAl upon Ar+ irradiation. They found that the saturation magnetization decreased, and an anomalous Hall resistivity progressively deviation from negative to positive was observed as a result of the structural deterioration.…”
Section: Crystallographic Defects In Heusler Alloysmentioning
confidence: 96%
“…For tetragonal X 3 Z (Z = Al, Ga, In Tl, Si, Ge, Sn, Pb) alloys, the X(A), X(B), X(C) and Z atoms occupy the (0, 0, 0), (0.25, 0.25, 0.25), (0.5, 0.5, 0.5) and (0.75, 0.75, 0.75) Wyckoff positions, respectively [22]. Thus, Chen et al [51] detected meta-stable tetragonal phase formation in Mn 2 CoAl upon Ar+ irradiation. They found that the saturation magnetization decreased, and an anomalous Hall resistivity progressively deviation from negative to positive was observed as a result of the structural deterioration.…”
Section: Crystallographic Defects In Heusler Alloysmentioning
confidence: 96%
“…Gaier studied He + and Ga + irradiation effects on several Co based Heusler-alloy thin films [191]. Chen P. et al investigated changes in the structural and magnetic properties of 27 nm Mn2CoAl thin films irradiated with 30 keV Ar + ions, observing an increase in lattice constant, a decrease in saturation magnetization, and changes in Hall resistance [192]. Additionally, I. Abdallah et al explored the effects of 150 keV He + irradiation on 40 nm Co2MnSi thin films as a substitute for annealing to induce B2 order, noting a reduction in magnetization with increasing fluence, and later, they reported structural effects as well [193]- [195].…”
Section: Modification In Ferromagnetic Thin Films and Multilayer Stacksmentioning
confidence: 99%